THE RELATIONSHIP BETWEEN MATERNAL BEHAVIOR AND THE COMPLETENESS OF BASIC INFANT IMMUNIZATION AT THE SINAR BARU BANGKA HEALTH CENTER 2024 - Afriany, Evi; Siswanto, Siswanto; Kusmadeni, Deri (HEARTY, 2025)
The results of the immunization program indicator achievement in 2023 are a big record for the Ministry of Health. Based on the results of immunization achievements in 2023, it has not met the expected target. This indicates that there is an underlying problem in maternal knowledge, attitudes, and actions related to immunization. This decrease in coverage can result in an increased risk of spreading diseases that can be prevented by immunization, so this study is very relevant. The purpose of this study is to determine the relationship between maternal behavior and the completeness of basic infant immunization at the Sinar Baru Health Center, Sungailiat District in 2024. This study uses a type of quantitative research with observational analysis using a cross sectional design. The results showed the relationship between mothers' knowledge about immunization and the completeness of basic childhood immunization with a value of p 0.001, the relationship between mothers' attitudes regarding immunization and the completeness of basic childhood immunization with a value of p 0.014, the relationship between mothers' actions regarding immunization and the completeness of basic childhood immunization with a value of p 0.004. The conclusion of the study is that there is a relationship between mothers' knowledge, attitudes and actions regarding immunization and the completeness of basic immunization of children.